P‐20: High Quality Self‐Aligned Coplanar Thin‐Film Transistors with SOG Materials for High Transparent AMOLED Display. Issue 1 (28th June 2022) - Liu, Wei; Song, Young Suk; Zhang, Xing; Liu, Fengjuan; Gu, Pengfei; Zhang, Jianye; Lu, Yuhang; Wang, Haoran; Sun, Hongda; Ning, Ce; Yuan, Guangcai
Abstract : We improved the performance of self‐aligned coplanar thin‐Film transistors with SOG Materials. In this work, the composition of TFT's buffer layer was changed by SOG Material to ensure the electrical performance of TFTs and high transparency of panel simultaneously. In addition, the shielding metal layer of self‐aligned top gate TFT was used as auxiliary cathode which can improve the uniformity of large size AMOLED display. We achieved 48% transparency of AMOLED display panel with 80PPI resolution ratio.